Utilization of radiometric data for mapping primary and secondary sources of gamma radiation and radon/thoron release potentials in Ireland - Aghdam, Mirsina M.; Kavanagh, Mark; Crowley, Quentin (Frontiers in Public Health, 2024)
Background This paper presents a novel approach to predict and map radon and thoron levels. We developed separate radon and thoron prediction maps for Ireland and introduced a system for producing high-resolution 3D radiation maps which may be used for planning purposes in residential areas, recycling and demolishing waste depots, and quarries of building and construction material. Additionally, we highlight the critical need to monitor thoron alongside radon in indoor surveys, as thoron’s shorter half-life and higher energy levels may pose a greater health risk. Methods We utilized Tellus radiometric survey data and indoor radon measurement records to investigate the spatial correlation between elevated indoor radon activity and anomalies in radioelement concentrations. We also estimated the degree of thoron interference in indoor radon surveys conducted in Ireland using CR-39 detectors. Field and laboratory surveys were performed to produce high-resolution radiation maps for four Irish quarries and estimate the radon and thoron potential of these quarries. Results Our initial findings suggest that thoron may be the primary health issue in some parts of Ireland, surpassing radon. For example, our map shows that the expected thoron potential in county Donegal is significantly higher than that for radon. Our radon and thoron exhalation tests on building material samples from four random quarries confirm this. We also estimate that over 20% of the elevated indoor radon activity recorded by the EPA using CR-39 detectors may be attributed to thoron-related sources. Conclusion This study contributes to a better understanding of the prevalence and impact of radon and thoron in Ireland, helping to determine the main radiological health issue related to indoor air quality in the country. Thoron’s impact on indoor air quality and health has been understudied in Ireland, necessitating more comprehensive studies and monitoring programs to accurately assess the prevalence and impact of both radon and thoron.